Answer:
f(-2) = -1
Step-by-step explanation:
One way of doing this is to substitute -2 for x in every place where x shows up:
f(x) = 4x + 3x^2 − 5 → f(-2) = 4(-2) + 3(-2)^2 − 5
→ f(-2) = -8 + 3(4) - 5, or f(-2) = 4 - 5, or f(-2) = -1
1/2-1/4
(1/2x2)-1/4
2/4-1/4
2-1
1
1/4
So for this problem we need to do order of operations so the very first step that we need to do here is (8+2) because that is the smallest enclosed symbols (8+2)=10 next divide by 20 because that is the next step in the equation which 20/10=2, so now we have {[2]^6+6} and due to order of operations the next step here is to take 2 to the power of 6 which is 64 so now we have {64+6} which is 70 so now we have 70/(4^2/2) and due to order of operations we do the parentheses first and that would mean that we do 4^2 because exponents come after parantheses like so,
70/(16/2) now we do 16/2 because its still inside the paranthesess so 16/2=8 so now we have 70/8 and that equals are end answer of 8.75 Enjoy!=)
-3(-4y+3) +7y
Expand
12y-9+7y
Add like terms
19y-9